Legality Analysis of Baros Mangrove Area Designation with the Status of Essential Ecosystem Area on Sultan Ground Land - Imam Amalda Rizki Harahap; Sunarya Raharja (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to answer the question of why Baros mangrove forest area does not yet have legal legality and the opportunities for this area to be used as an essential ecosystem area, Kawasan Ekosistem Esensial (KEE). This study used empirical normative research to integrate normative legal aspects at the level of theories, rules, and legal principles and empirical legal aspects, namely the application of law in social reality in society. The qualitative approach method is obtained from interviews, observations, recordings, and others. The novelty of this study is related to the study object and the procedure for the designation of the candidate for the Baros mangrove KEE, which is different from the previous KEE designation, which was only based on national law. At the same time, the KEE designation in D.I Yogyakarta uses two legalities. They are a KEE Decree Letter (National Law) and a Certificate of Land Rights on Sultanate land (Privilege Law). The study results found that there is already a wetland KEE management forum in the Special Region of Yogyakarta Province, which is contained in the Decree of the Governor of the Special Region of Yogyakarta Number 111/Kep/2022. Concluded that efforts to determine the Baros KEE mangrove forest area have great opportunities.